Antimicrobial activity of lavender (Lavendular angustifolia) oil against fish pathogenic bacteria isolated from cultured olive flounder (Paralichthys olivaceus) in Korea - Wimalasena, S.H.M.P.; Pathirana, H.N.K.S.; De Silva, B.C.J.; Hossain, Sabrina; Heo, Gang-Joon (Indian Journal of Fisheries, 2018)
The antibacterial activity of lavender (Lavendular angustifolia) essential oil (LVO) was tested against five Gram-negative and nine Gram-positive pathogenic bacteria isolated from cultured olive flounder (Paralichthys olivaceus) in Korea. Disc diffusion assay, minimum bactericidal concentration (MBC) and minimum inhibitory concentration (MIC) tests showed that growth of both Gram-negative and Gram-positive bacteria were inhibited by LVO. The inhibition zone diameter (IZD) increased in proportion to the LVO concentration for all of the fish pathogenic bacteria and the maximum effect was found at 100% (V/V) concentration of LVO. Streptococcus iniae was most sensitive to LVO while Edwardsiella tarda was most resistant. LVO was bacteriostatic (MBC/MIC>4) for all strains of S. iniae and bactericidal (MBC/MIC=1-4) for rest of the isolates, except one isoate of E. tarda. The antibiogram pattern indicated that all the bacterial strains excluding three strains of S. iniae (S186, S530 and S131) showed resistance to one or more antibiotics. Since antibacterial activity of LVO was considerably effective against fish pathogenic bacteria, their use could be effectively used to treat bacterial infections in aquaculture.